CAMPANARIO ARCHAEOLOGICAL COMPLEX AND THE PRESENCE OF INCISED AND APPLIQUE CASMA CERAMICS IN HUARMEY VALLEY, NORTH-CENTRAL COAST OF PERU - Zavaleta Paredes, Luis (2013)
Based on ceramic and architectural evidence collected from the archaeological complex of Campanario, we identify this site as the political and religious center in the valley of Huarmey around AD 1000. In this article we discuss the activity areas of Campanario and present detailed description of a local style of ceramic which we are calling the Campanario Style. Artifacts and features from surface contexts have allowed us to reconstruct the occupational history and site chronology of Campanario. The results of our analyses have furthered our understanding of the type of sociopolitical organization operating in the Huarmey Valley during the Late Intermediate Period (AD 900-1400).